Accuracy of an Extubation Readiness Test in Predicting Successful Extubation in Children With Acute Respiratory Failure From Lower Respiratory Tract Disease*. Issue 1 (January 2017) - Faustino, Edward Vincent S.; Gedeit, Rainer; Schwarz, Adam J.; Asaro, Lisa A.; Wypij, David; Curley, Martha A.Q.
Abstract : Objective: Identifying children ready for extubation is desirable to minimize morbidity and mortality associated with prolonged mechanical ventilation and extubation failure. We determined the accuracy of an extubation readiness test (Randomized Evaluation of Sedation Titration for Respiratory Failure extubation readiness test) in predicting successful extubation in children with acute respiratory failure from lower respiratory tract disease. Design: Secondary analysis of data from the Randomized Evaluation of Sedation Titration for Respiratory Failure clinical trial, a pediatric multicenter cluster randomized trial of sedation. Setting: Seventeen PICUs in the intervention arm. Patients: Children 2 weeks to 17 years receiving invasive mechanical ventilation for lower respiratory tract disease. Intervention: Extubation readiness test in which spontaneously breathing children with oxygenation index less than or equal to 6 were placed on FIO2 of 0.50, positive end-expiratory pressure of 5 cm H2 O, and pressure support. Measurements and Main Results: Of 1, 042 children, 444 (43%) passed their first extubation readiness test. Of these, 295 (66%) were extubated within 10 hours of starting the extubation readiness test, including 272 who were successfully extubated, for a positive predictive value of 92%. Among 861 children who were extubated for the first time within 10 hours of performing an extubation readiness test, 788 passed their extubation readiness test and 736 were successfully extubated for a positive predictive value of 93%. The median time of day for extubation with an extubation readiness test was 12:15 hours compared with 14:54 hours for extubation without an extubation readiness test within 10 hours ( p < 0.001). Conclusions: In children with acute respiratory failure from lower respiratory tract disease, an extubation readiness test, as described, should be considered at least daily if the oxygenation index is less than or equal to 6. If the child passes the extubation readiness test, there is a high likelihood of successful extubation. Abstract : Supplemental Digital Content is available in the text.